The Role of Citizen Participation in Environmental Governance for Sustainable Rural Development in Bayelsa State - Amatari-Breford, Sinclair Amatari; Tarilayefa , Clarke; Numoipre, Inainfe (Kashere Journal of Politics and International Relations, 2023)
Citizen participation in Environmental decision-making for environmental protection and sustainability is critically important. This paper aimed to evaluate citizen participation in environmental decision-making in sampled area, with key objective to identify factors affecting citizen participation. The study area comprises ten oil and gas bearing communities within the Nun River Oilfield in Bayelsa State. Primary data were collected through the survey method, where a well-structured questionnaire was administered on 390 respondents in all sampled communities selected through the simple random sampling technique. Data were both descriptively and statistically analysed. The results of the descriptive analyses showed low participation between communities. Similarly, results of an ANOVA test showed that F-ratio calculated 1527.552 was greater than tabulated value of 3.84, and P-value 0.000 was less than significant 0.05 suggesting low participation in environmental control significantly varied among individuals and communities. Results also showed significant relationship with socioeconomic characteristics and participation: income and educational attainment and participation. 76℅ of respondents were unaware of relevant environmental laws and the consequences of their harmful anthropogenic activities, while 24% stated been aware, but blamed income level, illiteracy and nature of subsistence occupation for engaging in such activities. Results also showed that 68% of respondents were willing to participate. The researchers recommended that Government at all levels should should seek citizens and stakeholder’s involvement in the formulation and implementation regimes of environmental control programmes, and organise awareness or enlightenment programmes to educate the citizens on the need to strike a balance between socioeconomic development and environmental sustainability.